Abstract Sa702: Gender Differences in Sudden Cardiac Death During Endurance Racing: The Role of Behavioral Responses to Competition ? - Chabrol, Marion; Chocron, Richard; Laurenceau, Thomas; BEGANTON, Frankie; Bougouin, Wulfran; Empana, Jean-Philippe; Jouven, Xavier (Circulation (New York, N.Y.), 2024)
Background: Men represent about 95% of Sudden Cardiac Death (SCD) that occur during sport activity. This over representation of men during exercise-related SCD which remains true even after adjustment for sport participation is not explained by biological and physiological factors. We hypothesized that male psychology and related behavioral responses might play a role in this over-representation. Methods: Data comes from the Paris Sudden Death Expertise Center. We collected the data from the last 10 years on the three most important running races in Paris: half marathon (HM), full marathon (FM) and 20 km. We analyzed the potential acceleration during the last km in men and women (only available for the HM (445,000 participations)), compared with the speed recorded during the previous 5km, each subject being its own control. We assessed the exact location of the SCD cases for each race. Using Artificial Intelligence (AI) and the electronic health record systematically collected for each subject in France (all drugs prescriptions, examinations and medical diagnoses), we assessed their theoretical risk for SCD. Results: Over the last 10 years and among the 1.2 million participants (mean age 38 ±11y, 71.6 % of males), there were 17 SCD (7 in 20km, 5 HM and 5 in FM). Of these, 88% (15/17) were men, with an average age of 42±13y. Incidence in men was 3-fold higher than women (16.9 vs 5.7 cases per million participations, p<1/1000). CPR was initiated by a bystander for 15 subjects ( 88.2%). Initial shockable rhythm was present in 13 subjects (76.5%). All 17 subjects were transported to hospital, either with a return of spontaneous circulation (15 (88.2%)) or in a refractory state (2 (11.8%)). At hospital discharge, 14 (82.4%) were alive with a very good neurological outcome (CPC1). Among all participants, 87%accelerated during the last km, during which 65% (11/17) of SCDs occurred (Figure 1). Compared with the previous 5km, women's speed varied little compared with men's over the last km (Figure 2). Among those who accelerated the most (>2 km/h) in the last km, the proportion of men was 1.96 times (CI 1.86-2.06) higher than that of women. On the basis of their medical history all but one of the subjects were considered as low risk for SCD by the IA algorithm. Conclusion: Although direct causality cannot be proven, men's attitude and behavioral reactions to competition could partly explain their over-representation in sport-related SCD.